1997
DOI: 10.1038/sj.bmt.1700877
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum HLA class I levels coincide with acute and chronic graft-versus-host disease

Abstract: Summary:More than two decades ago, the presence of naturally occurring soluble HLA class I molecules (sHLA-I) in the The ability to predict the likely occurrence of graftsera of healthy individuals was reported by van Rood et al 2 versus-host-disease (GVHD) after BMT would be and Charlton and Zmijewski. 3 Both groups defined these extremely valuable. We performed a retrospective study sHLA-I molecules by inhibition of HLA-specific alloantion the correlation between soluble HLA class I (sHLAsera in a complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In the first month after allotransplantation, a high sHLA class I level was found associated with aGVHD occurrence. Liem et al have already reported an increase of sHLA class I levels in bone marrow transplanted patients correlated with episodes of both acute and chronic GVHD [28]. This higher level of sHLA class I could be due to the release of sHLA class I molecules by damaged cells during aGVHD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the first month after allotransplantation, a high sHLA class I level was found associated with aGVHD occurrence. Liem et al have already reported an increase of sHLA class I levels in bone marrow transplanted patients correlated with episodes of both acute and chronic GVHD [28]. This higher level of sHLA class I could be due to the release of sHLA class I molecules by damaged cells during aGVHD.…”
Section: Discussionmentioning
confidence: 93%
“…However, 43% of those w/o aGVHD patients developed a chronic GVHD later (data not shown). Liem et al have already reported an increase of sHLA class I levels in bone marrow transplanted patients correlated with episodes of both acute and chronic GVHD [28]. Soluble HLA-G molecules are also involved in immune suppression and play a role in allograft acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…sHLA class I molecules are present in human sera and in the supernatant of lymphocyte cultures [3]. Their level is markedly increased in the sera of patients after bone marrow or organ transplantation in association with graft‐ versus ‐host disorders or episodes of rejection [4–6]. It is also increased in viral infections, autoimmune disorders and cancer [7–9].…”
Section: Introductionmentioning
confidence: 99%
“…AML and MDS were classified according to the French-American-British (FAB) system. 13,26 Antecedent hematologic disease (AHD) was defined as a documented abnormality in the blood count present for at least 1 month before presentation. One month is defined before presenting to MD Anderson Cancer Center, irrespective of whether therapy was initiated immediately or after the waiting period.…”
Section: Methodsmentioning
confidence: 99%
“…8 A recent study indicates that b2M, in addition to karyotype, may be a valuable prognostic marker in myelodysplastic syndrome (MDS). 9 After the discovery of free circulating HLA-I (sHLA-I) in serum, 10,11 it has been shown that these levels are increased in patients with evidence of cellular destruction, such as those with autoimmune diseases, 12 graft versus-host disease, [13][14][15] acute transplant rejection, 16 viral infection 17 and proliferating tumors. 18 In vitro data indicate that increased expression of surface HLA-I on tumor cells enhances their susceptibility to the cytolytic activity of T cells.…”
Section: Introductionmentioning
confidence: 99%